2013
DOI: 10.1002/open.201300009
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear d10‐ML2 Transition‐Metal Complexes

Abstract: We have investigated the molecular geometries of a series of dicoordinated d10-transition-metal complexes ML2 (M=Co−, Rh−, Ir−, Ni, Pd, Pt, Cu+, Ag+, Au+; L=NH3, PH3, CO) using relativistic density functional theory (DFT) at ZORA-BLYP/TZ2P. Not all complexes have the expected linear ligand–metal–ligand (L–M–L) angle: this angle varies from 180° to 128.6° as a function of the metal as well as the ligands. Our main objective is to present a detailed explanation why ML2 complexes can become bent. To this end, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 49 publications
6
61
0
1
Order By: Relevance
“…strong p backbonding). [29] Going from Pd(PH 3 ) 2 to Ag(PH 3 ) 2 + , we find a slightly more steeply increasing catalyst strain in an early stage of the reaction, despite the fact that both catalyst complexes have linear L-M-L angles in their equilibrium geometries. This shows that not the bite angle itself, but the intrinsic bite-angle flexibility of the catalyst is decisive for the reaction barrier.…”
Section: Metal Variation From Group 9 To Group 11mentioning
confidence: 92%
See 2 more Smart Citations
“…strong p backbonding). [29] Going from Pd(PH 3 ) 2 to Ag(PH 3 ) 2 + , we find a slightly more steeply increasing catalyst strain in an early stage of the reaction, despite the fact that both catalyst complexes have linear L-M-L angles in their equilibrium geometries. This shows that not the bite angle itself, but the intrinsic bite-angle flexibility of the catalyst is decisive for the reaction barrier.…”
Section: Metal Variation From Group 9 To Group 11mentioning
confidence: 92%
“…We have recently elucidated the reason for this bending. [29] Our analyses showed that L-M-L bending is favorable for d 10 M(L) 2 complexes with strong p backbonding, because the increase in steric repulsion is outweighed by a more strongly increasing stabilization that occurs when one of the two ligand p* acceptor orbitals overlaps and interacts with a different metal d orbital that is not yet stabilized by backbonding to the other ligand and therefore at a higher orbital energy.…”
Section: Metal Variation From Group 9 To Group 11mentioning
confidence: 94%
See 1 more Smart Citation
“…Figure S2. Profiles of the total energy E, the interaction energy E int , and the distortion energies E d (1) (for PdL) and E d (2) (for the allylic fragment) in kcal/mol versus the C-Cl distance in Å. The grey vertical lines mark the transition state locations (dotted=syn; solid=anti).…”
Section: S3mentioning
confidence: 99%
“…E_SCF (1) a E_SCF (2) Table 3. Orbital overlaps, orbital energies, charge transfer, electron density and the laplacian of the electron density at the Pd-Cl bond critical point along the reaction coordinate.…”
Section: Table S1mentioning
confidence: 99%